Impact of a Digital Health Coaching Program on Self-Efficacy and Medication Adherence in Diabetic Patients - Lee, Angel; Iskandar, Amirul (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to evaluate the effectiveness of a digital health coaching program in improving self-efficacy and medication adherence among patients with type 2 diabetes in Malaysia. A randomized controlled trial design was employed with 30 adult participants diagnosed with type 2 diabetes, recruited from healthcare centers in Malaysia. Participants were randomly assigned to an intervention group (n = 15), which received a 12-session digital health coaching program, or a control group (n = 15), which received standard care. The intervention was delivered over a period of 12 weeks, with a follow-up assessment conducted five months after baseline. Self-efficacy was measured using the Diabetes Management Self-Efficacy Scale (DMSES), and medication adherence was assessed using the Morisky Medication Adherence Scale (MMAS-8). Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests through SPSS-27. Descriptive results showed that the intervention group experienced a marked improvement in self-efficacy from pre-test (M = 52.47, SD = 6.21) to post-test (M = 65.20, SD = 5.38), which was sustained at follow-up (M = 63.93, SD = 5.67). Similarly, medication adherence in the intervention group increased from pre-test (M = 5.27, SD = 1.01) to post-test (M = 7.33, SD = 0.87) and remained high at follow-up (M = 7.13, SD = 0.92). Repeated measures ANOVA indicated significant time × group interaction effects for both self-efficacy (F(2, 56) = 22.91, p < .001) and medication adherence (F(2, 56) = 15.56, p < .001). Bonferroni post-hoc comparisons confirmed significant improvements in the intervention group over time, with no significant changes observed in the control group. The findings suggest that a structured digital health coaching program is an effective and sustainable approach to enhance self-efficacy and medication adherence in patients with type 2 diabetes, offering a scalable solution for improving diabetes self-management in diverse healthcare settings.